The Sphodrina of the southern Levant (Coleoptera: Carabidae, Sphodrini) - Casale, Achille; Assmann, Thorsten (Fragmenta entomologica, 2017)
Here we present a synthesis on the current knowledge of sphodrine carabids of the southern Levant (Israel, areas under Palestinian control, Lebanon, Jordan, Egypt east of Suez Channel: Sinai). A key for the identification of genera, subgenera and species is provided. Two new species are described: Taphoxenus (Lychnifugus) ziegleri sp. n. is described from Jordan (Type locality: Madaba), close to T. (L.) meridionalis Casale, 1988 (valid species), but markedly distinct for several characters both in external features and male genitalia. Laemostenus (Laemostenus) sinaiticus sp. n. is described from southern Sinai (Type locality: St. Catharina Monastery). This species belongs to the L. quadricollis species group (in the sense of Casale, 1988), and is close to L. aegyptiacus Schatzmayr, 1936. An updated key for the identification of the species of this group known so far in that area, which includes both epigean and subterranean species, is provided. The diagnostic features of all species newly described are illustrated, and their possible relationships are discussed. Furthermore, the features of male genitalia of Laemostenus (Laemostenus) aegyptiacus Schatzmayr, 1936 and Laemostenus (Laemostenus) libanensis (Piochard de la Brûlerie, 1876) are illustrated for the first time. The latter, known so far from the remains of the holotype specimen, is redescribed from material recently sampled in Lebanon.